DEVELOPMENT OF MYANMAR CARBOHYDRATE COUNTING BOOKLET - Win Thida Htwe; Wantanee Kriengsinyos; Chanida Pachotikarn; Nipa Rojroongwasinkul (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: Diabetes mellitus is one of the major challenging problems in Myanmar. Even with its high occurrence, the prevalence of good glycemic control was relatively low. According to Myanmar food culture, most of the foods that Myanmar people daily consumed are carbohydrate-based. Therefore, a nutrition education tool that can raise the awareness of amount of carbohydrate in foods and provide scientific but comprehensible dietary information about carbohydrate counting is necessaryin all arenas to combat diabetes: prevention, promotion and management. Aim: The aim of this study was to develop Myanmar carbohydrate counting booklet. Method: The first phase developed the booklet and then the acceptance of the booklet was assessed in the second phase by an experimental study. Results: In the first phase, the booklet named “Basic Carb Counting for People Living with DM” was developed. It was 14.5 × 20.5 × 1 cm in size and of 103 pages. It contained illustrated facts and information about diabetes, about basic carb counting and carb choices of different food items along with respective food photographs. In the second phase, 36 people with diabetes participated in the study with the mean age of 48.4 ± 10.7 years, 47.2% of male and 52.8% of female. The results showed that the knowledge score of diabetes, carbohydrate and total scores increased significantly (p <0.05) between pre-test score and post-test score. The participants’ satisfaction level with the newly developed booklet was somewhere between “very satisfied” to “extremely satisfied” giving the mean and median responses of between 5 and 6 on a 6-point Likert scale. Conclusion: The developed carbohydrate counting booklet was accepted by people with diabetes in Myanmar and the contents in the booklet were understandable to witness the improvement in the knowledge of the disease and basic carbohydrate counting concept as well.